1999
DOI: 10.1115/1.2832687
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Circular Braiding Process, Part 1: Theoretical Investigation of Kinematics of the Circular Braiding Process

Abstract: Circular braiding is a manufacturing process for making circular braided fabrics. Relative sliding of yarns during their interlacing motion introduces friction which limits the density of the braided fabric. A kinematic analysis is presented in this paper. Yarns’ absolute motion, relative sliding motion and twist motion in the convergent zone are found to be important quantities in braid kinematics that impact the final braid structure. The straight yarn assumption, which ignores the effect of interyarn forces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 4 publications
0
25
0
Order By: Relevance
“…Zhang et al [4,5] reported that the discrepancy between kinematic models and experiments increases with the friction and the number of spools. They modeled the axisymmetrical braiding process with a cylindrical mandrel and a 64-carrier machine.…”
Section: Previous Workmentioning
confidence: 99%
“…Zhang et al [4,5] reported that the discrepancy between kinematic models and experiments increases with the friction and the number of spools. They modeled the axisymmetrical braiding process with a cylindrical mandrel and a 64-carrier machine.…”
Section: Previous Workmentioning
confidence: 99%
“…Ko, Pastore, and Head (1989) wrote an industrial handbook that discussed in detail materials, formation, structural geometry, and engineering analysis of braids. Zhang, Beale, and Broughton (1999) found the motions of yarns, including relative sliding motion and twist motion in the convergent zone, to be important quantities in braid kinematics that impact the final braid structure.…”
Section: Introductionmentioning
confidence: 98%
“…Zhang et al [16] presented a kinematic model of yarn motion within the 'convergent zone' in a circular braid, focusing on the effects of yarn straightness and frictional forces on final yarn distribution. Kessels and Akkerman [17] and Akkerman and Villa-Rodríguez [18] developed modelling approaches to predict the final fibre angle on complex arbitrary biaxial braided preforms, accompanied by experimental validation.…”
Section: Introductionmentioning
confidence: 99%